The Principle of Restorative Justice in the Settlement of Children's Cases: A Literature Analysis of Practice in Indonesia - Ibrahim, Riza Andrian; Okta, Setyo Luthfi (International Journal of Humanities, Law, and Politics, 2025)
The implementation of restorative justice in Indonesia’s juvenile criminal justice system has become a significant paradigm shift aimed at prioritizing the best interests of the child. Through Law Number 11 of 2012 on the Juvenile Criminal Justice System (UU SPPA) and Supreme Court Regulation Number 4 of 2014, diversion is emphasized as an alternative to formal prosecution. This study analyzes the legal framework, implementation practices, challenges, and opportunities of restorative justice in resolving juvenile cases in Indonesia. Using a qualitative approach with juridical-normative and sociological-empirical methods, data were collected through literature review, in-depth interviews, and participant observations in Jakarta, Bandung, and Yogyakarta. Findings reveal that while restorative justice has legal support and cultural alignment with local values of deliberation and mutual cooperation, its implementation faces obstacles. These include inconsistent application by law enforcement officers, lack of specialized training, limited supporting facilities, and societal stigma toward child offenders. Active family and community involvement are identified as critical factors for successful reintegration, yet negative perceptions hinder effective restorative processes. The absence of systematic evaluation and monitoring further impedes sustainable implementation. This study recommends strengthening capacity building for law enforcement, increasing public education, enhancing infrastructure and facilities, and establishing structured evaluation mechanisms. Through collaborative efforts among stakeholders, restorative justice can be optimized as a humane and effective approach to rehabilitating juvenile offenders and fostering their reintegration into society.